(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the concept of domestic tourism, its main features, and its role in the country’s economy. The economic and social impact of domestic tourism, its contribution to the development of regional infrastructure, and its role in job creation are highlighted. Strategies for the development of domestic tourism, ways to attract investments, and ways to promote cultural and ecological tourism are also proposed. This article contains scientific and practical recommendations for ensuring the sustainable development of domestic tourism and can be useful for specialists conducting research in this field.